1994
DOI: 10.1203/00006450-199409000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Treatment of Infants at Risk for Chronic Lung Disease: Surfactant Components and Inflammatory Parameters in Airway Specimens

Abstract: The mechanisms explaining the beneficial effects of glucocorticoid in ventilator-dependent preterm infants are not known. In the present randomized trial, we evaluated the hypothesis that dexamethasone (DEX) treatment of small, preterm infants at risk for chronic lung disease favorably affects the surfactant system. Twenty-three ventilatordependent infants, with a mean +. SD gestational age of 26 ? 2 wk and a mean birth weight of 836 4 173 g, received 1 wk of treatment with either DEX (dose 0.5 mg/kg/d) or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…We also showed a reduced total protein content and a reduced MPO activity in tracheal aspirates, confirming previous findings in preterm infants with chronic lung disease (12)(13)(14)16,18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also showed a reduced total protein content and a reduced MPO activity in tracheal aspirates, confirming previous findings in preterm infants with chronic lung disease (12)(13)(14)16,18).…”
Section: Discussionsupporting
confidence: 91%
“…In preterm newborns with BPD, Kari et al showed that DEXA significantly decreased the nonsedimentable protein in epithelial lining fluid, whereas it did not affect the concentration of surfactant phosphatidycholine, 1L-1 〉 and lactoferrin (18). No data are available on the effect of corticosteroids on surfactant kinetics in human BPD.…”
mentioning
confidence: 99%
“…The effect is a decrease of morbidity [159], in spite of a brief period of suppression of the basal corticoid concentration. Postnatal glucocorticoid therapy shows no clear evidence of long term benefits [160]. However, the combined use of corticosteroids with surfactant improved the outcome of therapy compared with the use of surfactant alone [147].…”
Section: Therapeutic Effects Of Hormonesmentioning
confidence: 99%
“…14 Kari et al found no change in LF levels in ventilator-dependent infants, despite the increase in surfactant A in bronchial epithelium surface liquid as a result of dexamethasone application. 15 Although it might be considered that LF levels must be decreased by CSs, which is one of the main inhibitors of the immune system, common results of all these reported studies suggest that CSs exert no inhibitory effect on the innate immune system while 16 In this study, no effect of CS treatment was noted on tissue LF levels in patients with NP, even though there was a significant reduction in NP in response to CS treatment, as indicated by endoscopic and radiological findings. This study indicates that CS treatment may exert its beneficial clinical effect on NP by other mechanisms rather than via altering tissue LF levels.…”
Section: Discussionmentioning
confidence: 99%